Ocular Abnormalities in Stroke: Prevalence and Risk Factors in a Tertiary Care Hospital, South-East Nigeria - David O. Ukwu; Stella N. Onwubiko; Nkiru Z. Nwachukwu; Judith C. Ezike; Favour A. Onwuasoanya; Ferdinand C. Maduka-Okafor; Birinus A. Ezeala-Adikaibe; Rich E. Umeh (International Journal of Medicine and Health Development)
Background: Visual challenges have been associated with stroke. It can impede on the rehabilitation and impact on the quality of life of the patients. Objectives: We aimed to investigate the prevalence of ocular abnormalities in stroke patients and the risk factors in order to obtain baseline data for effective policy formulation on eye care as part of a multidisciplinary care for stroke patients at University of Nigeria Teaching Hospital, (UNTH) Enugu, Nigeria. Materials and Methods: The eyes of 110 consecutive stroke patients aged 18 years and above attending the Neurology clinic of UNTH were examined over a period of 6 months. Critically ill patients and those with known pre-morbid ocular pathology were excluded. Information on their sociodemographic and clinical profile was obtained using an interviewer-administered questionnaire. All participants underwent detailed ophthalmological evaluation. Descriptive and inferential statistics were used to analyze data. The association was tested with chi-square, and P < 0.05 was considered significant. Results: A total of 220 eyes of 110 participants comprising 63 (57.3%) males and 47 (42.7%) females were evaluated. The mean age of the participants was 62.09 ± 13.1 years. They had hypertension and diabetes mellitus as their co-morbid conditions. Ocular abnormalities were observed in 214 (97.5%), as follows: refractive error 66.4%, hypertensive retinopathy 49.9%, cataract 47%, diabetic retinopathy 32.7%, ocular motility disorders 31%, glaucoma 28.2%, ptosis 22.2%, and papilledema 0.9%. Age was the only associated risk factor for ocular abnormalities (P = 0.01). Conclusion: Stroke was invariably associated with ocular abnormalities. Mandatory ophthalmic evaluation, especially for elderly hypertensive and diabetic stroke patients, early intervention, and rehabilitation are advised to improve the vision and health-related quality of life of stroke survivors.